Kinetic Characteristics of FCC to Hexagonal Transformation in (Ge1Sb2Te4)(0.8)(Sn1Bi2Te4)(0.2) Chalcogenide Alloy for Phase Change Memory - Ahn, Dong-Ho; Kim, Hyun-Mi; Lee, Min-Hyun; Kang, Dae-Hwan; Cheong, Byung-ki; Kim, Ki-Bum (KOREAN INST METALS MATERIALS, 2005)
We examined the kinetic characteristics of the fcc to hexagonal transformation in a (Ge1Sb2Te4)(0.8)(Sn1Bi2Te4)(0.2) chalcogenide alloy mixture, which was utilized to propose a phase change memory in our recent study. Our examination involved in-situ measurement of temperature-dependent sheet resistance along with transmission electron microscopy (TEM) analysis. The (Ge1Sb2Te4)(0.8)(Sn1Bi2Te4)(0.2) alloy was found to transform from an as-deposited fcc crystalline phase to an hcp crystalline phase at 485 K; by contrast, Ge1Sb2Te4 transformed from an as-deposited amorphous phase to an fcc crystalline phase at 370 K. By use of Kissinger's method, we determined the activation energies of the transformations respectively as 1.85 eV for Ge1Sb2Te4 and 2.98 eV for (Ge1Sb2Te4)(0.8)(Sn1Bi2Te4)(0.2). The activation energy of 2.98 eV for (Ge1Sb2Te4)(0.8)(Sn1Bi2Te4)(0.2) was found to be lower than that of the fcc to hcp phase transformation of Ge2Sb2Te5. We consider that such a lower activation energy is partly responsible for a rapid fcc to hcp transition in the phase-change memory with (Ge1Sb2Te4)(0.8)(Sn1Bi2Te4)(0.2) as a memory material.
Keywords: FILMS